2002
DOI: 10.1093/hmg/11.26.3333
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of pathology in mdx mice by expression of utrophin: analysis using an inducible transgenic expression system

Abstract: Duchenne muscular dystrophy results from the absence of dystrophin, a cytoskeletal protein. Previously, we have shown in a transgenic mouse model of the disease (mdx) that high levels of expression of the dystrophin-related protein, utrophin can prevent pathology. We developed a new transgenic mouse model where muscle specific utrophin expression was conditioned by addition of tetracycline in water. Transgene expression was turned on at different time points: in utero, at birth, 10 and 30 days after birth. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
99
1
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(111 citation statements)
references
References 41 publications
5
99
1
6
Order By: Relevance
“…Alternatively, such an approach has to be associated with a second treatment, which avoids muscle degeneration. This latter result may be obtained using different strategies, including a gene therapy approach allowing for dystrophin, mini-or microdystrophin expression; 23 gene transfer-mediated overexpression of utrophin; 28 antisense approaches consisting of the delivery of oligonucleotides (or rAAVs allowing their production) targeted to splicing elements of the dystrophin pre-mRNA that can induce exon skipping and thereby restore the open reading frame and the production of a functional dystrophin; 29 ribosomal readthrough of premature termination codons by compounds such as PTC124; 30 or pharmacological treatment to increase levels of utrophin. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, such an approach has to be associated with a second treatment, which avoids muscle degeneration. This latter result may be obtained using different strategies, including a gene therapy approach allowing for dystrophin, mini-or microdystrophin expression; 23 gene transfer-mediated overexpression of utrophin; 28 antisense approaches consisting of the delivery of oligonucleotides (or rAAVs allowing their production) targeted to splicing elements of the dystrophin pre-mRNA that can induce exon skipping and thereby restore the open reading frame and the production of a functional dystrophin; 29 ribosomal readthrough of premature termination codons by compounds such as PTC124; 30 or pharmacological treatment to increase levels of utrophin. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Les approches développées pour stimuler l'expression d'utrophine chez la souris mdx adulte ont, tout au plus, permis d'augmenter celle-ci de 2 à 3 fois, nettement moins que dans la lignée transgénique Fiona, où aucun signe de dystrophie n'était plus détectable. Les résultats obtenus avec la transgenèse conditionnelle [25] indiquent que la quantité-seuil requise pour corriger un paramètre déficitaire diffère selon le paramètre considéré. La dystrophie ne pourra être vaincue que lorsque la quantité d'utrophine nécessaire à la correction du(des) paramètre(s) responsable(s) aura été obtenue.…”
Section: Discussionunclassified
“…Ce contrôle est réversible et offre la possibilité de déclen-cher ou de réprimer l'expression du transgène à n'importe quel moment de la vie de l'animal. Ce type de construction génétique a été développé pour l'expression conditionnelle de l'utrophine dans les muscles de souris mdx à différents moments (avant et après la naissance), suivie d'une analyse de l'état dystrophique des muscles à l'âge adulte (3 mois) [25]. Quantitativement, la surexpression par rapport à l'état mdx est modérée, bien inférieure à celle obtenue dans la lignée transgénique Fiona.…”
Section: Transgenèse Conditionnelleunclassified
See 1 more Smart Citation
“…28,29 In support of this idea, transgenic mice lacking both dystrophin and utrophin have severe muscle disease that more closely resembles Duchenne dystrophy 30,31 and increased transgenic expression of utrophin reduces the muscle pathology in the mdx mouse. 32,34 In a preceding paper, we showed that genetic depletion of utrophin in muscle fibers from mdx mice produces a gene dosedependent increase in the opening probability of single MS channels in recordings from membrane patches. 35 The increase in MS channel opening in the utrophin mutants lasted seconds rather than milliseconds.…”
Section: Introductionmentioning
confidence: 99%